(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study on relationship between metabolic syndrome and oral health, is rare. We investigated to find out the correlation of metabolic syndrome and oral health. We investigated to find out the correlation of metabolic- syndrome and oral health with the data from the 6th Korea- National- Health and Nutrition- Examination- Survey. This is the cross-sectional designed study. 2433 subjects (aged 50 ≤) were included. Metabolic- syndrome was defined as NCEP-ATP (National- Cholesterol- Education- Program-Adult- Treatment- Panel Ⅲ). To analyze influencing factors of metabolic syndrome, multi-variable- logistic- regression was used. Our results showed that gender(male) (OR 1.86; 95%CI: 1.27-2.72; p<.05) and not taking dietary supplements (OR 1.74; 95%CI: 1.22-2.48; p<.05) factors were the most influencing factors of metabolic syndrome. And then, presence of stress(OR1.59; 95%CI: 1.28-1.98; p<.05), lowest education level(elementary)(OR1.48; 95%CI: 0.98-2.21; p=.05), and oral health(periodontitis) (OR1.39; 95%CI: 1.09-1.78; p<.05) factors were showed as the next strong factors of metabolic syndrome in order. While chewing ability was not related with metabolic syndrome. We highlighted on the impact of oral health in metabolic syndrome including chewing difficulty as well as periodontitis. And to prevent metabolic syndrome cause of serious disability and lowering quality of life, we tried to find out the influencing factors of metabolic syndrome considering of this study with diverse view point such as adding the dietary supplements as dietary habit, stress as psychological value, and sedentary time as health-related factors. The government and public health associates should do urgently preparing the policies and strategies focusing on gender disparities, dietary supplements and oral health to prevent metabolic syndrome among ageing population.